Status of infectious disease content in the professional pharmacy curriculum in Saudi Arabia: Results of a national survey - Fulwah Y. Alqahtani; Safiah H. Alattas; Thamer A. Almangour; Fadilah S. Aleanizy (Elsevier, 2021)
Objectives: Antimicrobial resistance is one of the main global problems faced by healthcare institutions. Healthcare professionals as service providers must have a basic understanding of this emerging threat; additionally, considering the evolving role of pharmacists in both the community and hospital setting, it is crucial that pharmacists are part of the fight against this threat. Therefore, this study aimed to assess infectious disease subjects covered in the pharmacy curriculum in Saudi Arabia, to evaluate teaching and knowledge assessment strategies concerning infectious diseases, and to explore challenges faced by faculty members in teaching infectious disease courses. Methods: We constructed a questionnaire with 26 items and sent it to infectious disease faculty members at 26 Saudi Arabian pharmacy colleges. It included questions regarding the faculty and institution, infectious disease topics, hours dedicated to each topic, and tools and strategies used in the courses for better understanding and assessment of students. In addition, we enquired about the faculty members' current satisfaction of, and future plans for, the curriculum. Results: The questionnaire was completed by infectious disease faculty members, department chairs, or college deans. Among the respondent schools, 85.5% were governmental and 14.5% were private institutions. The majority of colleges (98.2%) followed a semester format schedule, with 67.3% offering solely the Doctor of Pharmacy (PharmD) program. More than 78% of respondents covered all tier 1 infectious disease topics from the American College of Clinical Pharmacy Pharmacotherapy Didactic Curriculum Toolkit. The main tool used for teaching was lectures (94.5%), while patient case application was the main teaching strategy (54.5%). Approximately 63% of respondents thought that the curricula were adequate when they were asked about their opinion of the curricula coverage, and 63.64% thought that the curriculum provided adequate baseline knowledge on infectious diseases for the following 5 years. Conclusions: The study revealed variations in infectious disease topics covered and the time dedicated to them among pharmacy colleges in Saudi Arabia. The faculty members who responded to our questionnaire were generally satisfied with their infectious disease curriculum. To the best of our knowledge, this is the first study to assess infectious disease curricula among Saudi pharmacy colleges. Thus, the findings of this study may encourage faculty members to advocate for the standardization of infectious disease courses offered at Saudi Arabian pharmacy colleges.